Apocynin, a Low Molecular Oral Treatment for Neurodegenerative Disease. (21st July 2014) - 't Hart, Bert A.; Copray, Sjef; Philippens, Ingrid
Abstract : Accumulating evidence suggests that inflammatory mediators secreted by activated resident or infiltrated innate immune cells have a significant impact on the pathogenesis of neurodegenerative diseases. This may imply that patients affected by a neurodegenerative disease may benefit from treatment with selective inhibitors of innate immune activity. Here we review the therapeutic potential of apocynin, an essentially nontoxic phenolic compound isolated from the medicinal plant Jatropha multifida . Apocynin is a selective inhibitor of the phagocyte NADPH oxidase Nox2 that can be applied orally and is remarkably effective at low dose.